Dreaming blackness : black nationalism and African American public opinion - Price, Melanye T. (NYU Press, 2009)
Black Nationalism is one of the oldest and most enduring ideological constructs developed by African Americans to make sense of their social and political worlds. In Dreaming Blackness, Melanye T. Price explores the current understandings of Black Nationalism among African Americans, providing a balanced and critical view of today?s black political agenda. She argues that Black Nationalism continues to enjoy moderate levels of support by most black citizens but has a more difficult time gaining a larger stronghold because of increasing diversity among blacks and a growing emphasis on individu.